Investigation of magneto-optical properties of magnetic fluid for fiber optics applications - Zu, Peng (2014)
Magnetic fluid (MF) is a novel kind of magneto-optical functional material that possesses diverse magneto-optical properties such as tunable refractive index, birefringence effect, dichroism effect, Faraday effect, field dependent transmission property and so on. It can serve as the magnetically sensitive material playing the key role in magnetic field sensors and magneto-optical devices. There were many reported photonic devices based on MF in the literatures. This thesis focuses on investigating the magneto-optical properties ofMF for fiber optics applications